1997
DOI: 10.1063/1.364852
|View full text |Cite
|
Sign up to set email alerts
|

High density recording with keepered media and planar heads

Abstract: Modeling and experimental results are presented for keepered longitudinal recording media and planar (undershoot-reduced) thin film recording heads with low flying heights for areal densities >1 Gb/in.2. The keeper layer is magnetically coupled to the medium magnetic transitions, reducing the transition demagnetization and narrowing the transition length by about 10% in the media after recording. The reproduced bias field and the transition fields combine in the keeper to produce a partially saturated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…They found that the pulse sharpening of keepered recording observed by Gooch, et aI., can be accompanied by time-shifts and time asymmetries. Work by Coughlin et al [19,20] also revealed asymmetric pulse amplitude. These nonlinearities are apparently caused by the relatively large fields produced in the keeper layer by the recorded transition, Figure 2.…”
Section: Read Processmentioning
confidence: 88%
See 1 more Smart Citation
“…They found that the pulse sharpening of keepered recording observed by Gooch, et aI., can be accompanied by time-shifts and time asymmetries. Work by Coughlin et al [19,20] also revealed asymmetric pulse amplitude. These nonlinearities are apparently caused by the relatively large fields produced in the keeper layer by the recorded transition, Figure 2.…”
Section: Read Processmentioning
confidence: 88%
“…Off the sides of the head, however, the reluctance of the intervening air gap and the shunting effect of the keeper cause the fields to drop more rapidly than normal. Measurements of trackprofiles reveal a reduction in write-width of 5% [20). More significantly, the side erase-bands [24] have been measured to drop by a factor of two (see section VII B).…”
Section: B Off-track Effectsmentioning
confidence: 93%
“…Before undertaking IRM curve measurements, the samples were demagnetized using the DC cyclic erasure process (DCE) [5]. This is done by taking M-H loops at gradually reduced values of maximum field.…”
Section: Methodsmentioning
confidence: 99%
“…However, we have previously studied traditional longitudinal media with a soft underlayer, i.e., so-called "keepered media" [5]. These films had a CoCrPt recording layer with a NiFe underlayer.…”
Section: Effect Of a Soft Underlayer On Coupling In Longitudinal Fmentioning
confidence: 99%
“…In the quest for increasing the areal densities of rigid and flexible magnetic recording media, a keepered magnetic recording media was proposed (Loven, 1994; Coughlin, 1996, 1997; Reed, 1996; Wood, 1997). It was made essentially by adding a thin layer of soft‐magnetic material (keeper layer) above (or under) the hard‐magnetic storage layer.…”
Section: Introductionmentioning
confidence: 99%